Research on DNA Sequence Homology Based on Second Order Markov Model (Journal of Fiber Bioengineering and Informatics, 2015)
DNA sequence homology is a critical and fundamental problem in bioinformatics. In this paper, wesolve this problem by use of the second order Markov modal instead of traditional sequence alignmentbecause DNA character sequence meets the Markov properties. Hence, the characteristics of DNAsequences are represented by using their two-step transition probabilities matrices. The similarity degreemeasurement between two different DNA sequences is defined. Our DSHM algorithm is put forwardwhich is implemented by MyEclipse. The contrast experiments are done between DSHM and other twomethods. The experimental results show that DSHM algorithm can determine DNA sequence homologycorrectly in the more effective way.
Keywords: DNA Sequence Homology; Similarity Degree; Second Order Markov Model